Cucurbitacin IIa interferes with EGFR-MAPK signaling pathway leads to proliferation inhibition in A549 cells. (October 2019) - Zhang, Jie; Song, Yifan; Liang, Yuan; Zou, Haoyang; Zuo, Peng; Yan, Mi; Jing, Siyuan; Li, Tiezhu; Wang, Yongjun; Li, Da; Zhang, Tiehua; Wei, Zhengyi
Abstract: Cucurbitacin IIa (CuIIa), a tetracyclic triterpenoid harboring anticancer activity, was investigated in A549 cells to reveal its mechanism of targeting on epidermal growth factor receptor (EGFR) signaling pathway. Results showed that CuIIa was capable of inducing apoptosis and cell cycle arrest at G2/M phase. The transcription of EGFR pathway genes and their proteins accumulation was inconsistently influenced by CuIIa. Notably, transcription of Raf1 was significantly upregulated, nevertheless, MEK1 and ERK1 were significantly downregulated. On the other hand, the accumulation of the total and phosphorylated proteins of the most members in EGFR-mitogen-activated protein kinase (MAPK) pathway, as well as CylclinB1 and survivin were also shifted by CuIIa treatment. Remarkably, total MEK remained constant but survivin completely degraded. Moreover, phosphorylated BRAF continuously increased while Raf1 and MEK decreased continuously. CuIIa was further confirmed to be a tyrosine kinase inhibitor (TKI) of EGFR by kinase inhibition assay. The results of molecular simulation showed that the long side chain of CuIIa occupied the binding pocket of EGFR and the ligand was stabilized at the active site of EGFR. In view of the results above, it is suggested that CuIIa inhibits cell proliferation by interfering the EGFR-MAPK signaling pathway. Highlights: CuIIa induces apoptosis and cell cycle arrest in A549 cells. CuIIa alters the existence status of participants in EGFR-MAPK pathway. CuIIa acts as a TKI of EGFR with a low IC50 value. CuIIa is stabilized at the active site in the binding pocket of EGFR.